Deep learning-based classification of eye diseases using Convolutional Neural Network for OCT images - Elkholy, Mohamed; Marzouk, Marwa A. (Frontiers in Computer Science, 2024)
Deep learning shows promising results in extracting useful information from medical images. The proposed work applies a Convolutional Neural Network (CNN) on retinal images to extract features that allow early detection of ophthalmic diseases. Early disease diagnosis is the critical key of retinal treatment. Any damage occurs to retinal tissues cannot be recovered and result in permanent degradation or even complete loss of sight. The proposed deeplearning algorithm detects three different diseases from features extracted from Optical Coherence Tomography (OCT) images. The deep-learning algorithm uses CNN to classify OCT images into four categories. The four categories are Normal retina, Diabetic Macular Edema (DME), Choroidal Neovascular Membranes (CNM), and Age-related Macular Degeneration (AMD). The proposed work uses publicly available OCT retinal images as a dataset. The experimental results shows significant enhancement in classification accuracy while detecting the features of the three listed diseases.